El Excentrico, 1974-09-20 - Garcia, Humberto:::Publisher::::::::::::; Garcia, Bert:::Manager::::::::::::; Garcia, Marc:::Editor:::::::::::: (Garcia Printing; San Jose, California, 2023)
September 5, 1974 [5 de septiembre de 1974]. No volume or issue number. Cover has photograph of Toni Sanchez, nominated Señorita Mexico 1974.